Predicting Cerebral Amyloid Angiopathy-Related Intracerebral Hemorrhages and Other Cerebrovascular Disorders in Alzheimer’s Disease - Yamada, Masahito (Frontiers in Neurology, 2012)
Cerebral amyloid angiopathy (CAA) of amyloid β-protein (Aβ) type is common in Alzheimer’s disease (AD). Aβ immunotherapies have been reported to induce CAA-related intracerebral hemorrhages (ICH) or vasogenic edema. For the purpose of developing a method to predict CAA-related ICH and other cerebrovascular disorders in AD, the biomarkers and risk factors are reviewed. The biomarkers include (1) greater occipital uptake on amyloid PET imaging and a decrease of cerebrospinal fluid Aβ40 levels as markers suggestive of CAA, and (2) symptomatic lobar ICH, lobar microhemorrhages, focal subrachnoidal hemorrhages/superficial siderosis, cortical microinfarcts, and subacute encephalopathy (caused by CAA-related inflammation or angiitis) as imaging findings of CAA-related ICH and other disorders. The risk factors include (1) old age and AD, (2) CAA-related gene mutations and apolipoprotein E genotype as genetic factors, (3) thrombolytic, anti-coagulation, and anti-platelet therapies, hyertension, and minor head trauma as hemorrhage-inducing factors, and (4) anti-amyloid therapies. Positive findings for one or more biomarkers plus one or more risk factors would be associated with a significant risk of CAA-related ICH and other cerebrovascular disorders. To establish a method to predict future occurrence of CAA-related ICH and other cerebrovascular disorders in AD, prospective studies with a large number of AD patients are necessary, which will allow us to statistically evaluate to what extent each biomarker or risk factor would increase the risk. In addition, further studies with progress of technologies are necessary to more precisely detect CAA and CAA-related cerebrovascular disorders.